1993
DOI: 10.1161/01.atv.13.8.1171
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of clopidogrel on platelet adhesion and intimal proliferation after arterial injury in rabbits.

Abstract: The possible activity of ticlopidine and its analogue clopidogrel in early atherogenesis was investigated. Incubation of rabbit platelets with the extracellular matrix produced by endothelial cells in culture induced massive platelet adherence in vitro. This phenomenon was strongly reduced when platelets were isolated from rabbits that had been treated with a single dose of clopidogrel (10 after mechanical dilatation of a coronary stenosis by means of a percutaneous transluminal coronary angioplasty (PTCA), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
1
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 32 publications
2
56
1
2
Order By: Relevance
“…52 These findings may explain the anti-restenotic effect of clopidogrel seen in an earlier animal model. 63 Recent data obtained with the active metabolite of clopidogrel and human platelets in vitro has reproduced the inhibitory effects of clopidogrel on platelet P-selectin expression and platelet/ polymorphonuclear neutrophil adhesion. Furthermore, these data have demonstrated an inhibitory effect of the clopidogrel active metabolite on platelet-dependent production of reactive oxygen species in neutrophils and on monocyte expression of tissue factor activity.…”
Section: Studies In Healthy Volunteersmentioning
confidence: 91%
“…52 These findings may explain the anti-restenotic effect of clopidogrel seen in an earlier animal model. 63 Recent data obtained with the active metabolite of clopidogrel and human platelets in vitro has reproduced the inhibitory effects of clopidogrel on platelet P-selectin expression and platelet/ polymorphonuclear neutrophil adhesion. Furthermore, these data have demonstrated an inhibitory effect of the clopidogrel active metabolite on platelet-dependent production of reactive oxygen species in neutrophils and on monocyte expression of tissue factor activity.…”
Section: Studies In Healthy Volunteersmentioning
confidence: 91%
“…This antagonism is non-competitive, irreversible, and results in 50-70% inhibition of platelet fibrinogen binding. Previous studies have demonstrated that clopidogrel reduces formation of both arterial (Hechler et al 1998) and venous (Herbert et al 1993) thrombi. Therefore, in the present study, we aimed to investigate whether clopidogrel would restore or at least decrease the harmful effects of ischemia-reperfusion via its antiaggregant effects.…”
Section: Biochemical Assaysmentioning
confidence: 96%
“…17,18 Like ticlopidine, clopidogrel is devoid of direct antiplatelet effects and must undergo hepatic metabolic modification to exhibit selective inhibition of ADP-induced platelet aggregation. 22 Clopidogrel acts by irreversibly inactivating platelet ADP receptor-initiated signaling in a dose-dependent manner.…”
mentioning
confidence: 99%